Política de motivación a los funcionarios de la Jefatura Provincial de Los Ríos de la CTE - Quiñonez Alcivar, Isabel Maria (2020)
The present work consists of creating a policy in which the Public Officials of the CTE of the Province of Los Ríos are motivated, have a better job stability and be in a suitable space to have a better functioning in the labor area. It is necessary to study the characteristics that are common in the public sector, such as the set of people, objectives, structures, resources, contexts, results and administrative systems. Motivation must be understood as the fabric that supports the development of those activities that are significant. for the person and in which he takes part, and in this way to be able to indicate that, motivation is an important aspect in the orientation of actions and forms a central element that leads people to achieve their objectives. Etymologically, the term motivation comes from the Latin motus, which is related to what mobilizes the person to carry out an activity for what is “the set of reasons why people behave in the ways they do, the behavior it is vigorous, directed and sustained”. The study is aimed at describing the motivational factors of public servants in Ecuador and comparing their relationship, considering as empirical objectives the description and comparison of possible differences in motivational factors within a group of public companies.